Announcement Return of The Acquirer and Payment Methods - Tran, Huong Trang (2012)
Mergers and acquisitions (M&A) have recently increased in both the number of deals and the deal value. They are undertaken by firms to obtain particular strategic and financial purposes. Previous studies on mergers and acquisitions present various results of the impact of M&A on the wealth value of the bidding firm’s shareholders. This study investigates the short-term performance of total 139 U.S public acquirers, engaging in 161 deals over the period of 2007-2011. Event study is adopted to examine the relationship between payment methods and abnormal return on the basis of target types, bidder size, book-to-market ratio and merger types. The standard market model and the event window of [-5, +5] are employed. The results differ based on the characteristics of the deals. However, in general, the findings indicate that cash financing method brings higher return for shareholders than stock financing method for the acquiring firms. In addition, private held firms often gain more benefits than public held firms. Most of the findings are consistent with the literature and prior research.